Appearing Stones. The Sacred Wood of Bomarzo - Jacoviello , Stefano (E|C, 2023)
The Sacred Wood of Bomarzo has been the subject of extensive iconological research aimed at deciphering the allegories with which it is strewed. Rather than devoting to deciphering the symbols, this article investigates the semiotic mechanism of the Sacred Wood, which concerns the simultaneous construction of different enunciative axes in a complex discoursive device that simultaneously includes illusion and simulation. Diverse configurations of the matter – stone, statue, creature, each relating to an order of the world –, produce different effects of presence in space and time that characterise the aesthetic experience of the place. In the tight confrontation between the human and the inhuman, the natural and the unnatural, the stones show themselves to be far from being inert material. Stones emerge from the ground, appear as elements in the landscape, stage themselves as such, and then they hide behind the machine of representation that asks to be evaluated by the visitor as art, nature, or simple artifice. Through the oscillation between looking and being looked at, the appearing of Bomarzo’s stones manifest the place of a crisis of the human dimension, and at the same time offer the antidote to exorcise it by coming to terms with time, passions, and the certainty that, after all, life is deception.